Are beliefs and attitudes about COVID-19 associated with self-perceived changes in food consumption? Results from a nationwide survey during lockdown - Martins, R.; Capitão, C.; Fialho, M.; Feteira-Santos, R.; Virgolino, A.; Santos, R. R.; Alarcão, V.; Silva, M.; Arriaga, M.; Graça, P.; Gregório, M. J.; Santos, O. (Appetite, 2022)
This study aimed to understand how beliefs and attitudes regarding COVID-19 are associated with self-perceived changes in food consumption during lockdown between March 19 and May 2, 2020. We conducted a cross-sectional study with a non-probabilistic weighted sample of the Portuguese population. Data were collected using an online survey and telephone interviews. The association between agreement with sentences about food and COVID-19 and perceived changes in food consumption were assessed by multinomial logistic regression models. Overall, 5858 citizens were included, with a mean age of 38.2 (17.3) years. Exclusive agreement with the belief “SARS-CoV-2 can be transmitted by food” (27.5%) was associated with decreased odds of perceived positive changes (e.g., increased consumption of fruit and vegetables). Agreement only with the attitudinal sentence “I started to consume foods that may protect against COVID-19” (11.9%) was associated with positive perceived consumption changes (e.g., increasing fruit and vegetables, and decreasing soft drinks and snacks). Cumulative agreement (with both sentences; 10.6%) was also associated with mostly positive food consumption changes. Specific beliefs and attitudes regarding COVID-19 and food are associated with self-perceived changes in food consumption. Longitudinal research is needed to understand how beliefs and/or attitudes about the role of food in infectious diseases act as determinants of eating behavior modification.